2005
DOI: 10.1657/1523-0430(2005)037[0025:sathov]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Heterogeneity of Vegetation Properties among Four Tundra Plant Communities at Ivotuk, Alaska, U.S.A

Abstract: Intraseasonal patterns of normalized difference vegetation index (NDVI), leaf area index (LAI), and phytomass were compared for four tundra vegetation types at Ivotuk, Alaska, during summer 1999. The vegetation types included moist acidic tundra (MAT), moist nonacidic tundra (MNT), mossy tussock tundra, and shrub tundra. The seasonal curves of NDVI were similar among the vegetation types but with varying magnitudes of the peak values. Peak NDVI in the shrub tundra (0.83) was significantly greater than in MAT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 32 publications
2
51
0
Order By: Relevance
“…NDVI is therefore frequently used to evaluate vegetation changes in high latitude environments [1,[6][7][8][9][10][11][12][13][14][15][16]. One of the previous analyses at the site of interest for this study (Ivotuk, Alaska) showed that, at the landscape scale, broad-band NDVI obtained by averaging hyperspectral bands across red and near infrared (NIR) regions had the greatest peak growing season values for shrub tundra (ST), compared to three other tundra plant communities [17]. While NDVI may be useful for separating some communities at peak growing season, it may be problematic during the early or late growing season when vegetation communities are more similar (Figure 1).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…NDVI is therefore frequently used to evaluate vegetation changes in high latitude environments [1,[6][7][8][9][10][11][12][13][14][15][16]. One of the previous analyses at the site of interest for this study (Ivotuk, Alaska) showed that, at the landscape scale, broad-band NDVI obtained by averaging hyperspectral bands across red and near infrared (NIR) regions had the greatest peak growing season values for shrub tundra (ST), compared to three other tundra plant communities [17]. While NDVI may be useful for separating some communities at peak growing season, it may be problematic during the early or late growing season when vegetation communities are more similar (Figure 1).…”
Section: Introductionmentioning
confidence: 95%
“…The primary study site of Ivotuk, Alaska (68.49˝N, 155.74˝W) is located on the North Slope of the Brooks Mountain Range [8,17,54] and was one of seven sites established as part of the Arctic Transitions in the Land-Atmosphere System (ATLAS) project [16,55,56]. Ivotuk is part of the Western Alaska Transect that starts in the north at Barrow and goes south through Atqasuk and Oumalik to Ivotuk [16,42,55,57].…”
Section: Study Sitesmentioning
confidence: 99%
See 3 more Smart Citations